2018
DOI: 10.1186/s40069-018-0246-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Fresh and Hardened Stage Properties of Self-Compacting Concrete using Random Kitchen Sink Algorithm

Abstract: High performance concrete especially self compacting concrete (SCC) has got wide popularity in construction industry because of its ability to flow through congested reinforcement without segregation and bleeding. Even though European Federation of National Associations Representing for Concrete (EFNARC) guidelines are available for the mix design of SCC, large number of trials are required for obtaining an SCC mix with the desired engineering properties. The material and time requirement is more to conduct su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Sathyan et al [2] used random kitchen sink algorithm and regularized least square to predict concrete rheological and hardened properties, with 32 data sets (80%) used for training and 8 datasets (20%) for testing. Revathy et al [3] used various types of network functions, one of the types using algorithm BFGS quasi-Newton back propagation, indicated using 34 datasets for training, 8 for validation and 8 for testing.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Sathyan et al [2] used random kitchen sink algorithm and regularized least square to predict concrete rheological and hardened properties, with 32 data sets (80%) used for training and 8 datasets (20%) for testing. Revathy et al [3] used various types of network functions, one of the types using algorithm BFGS quasi-Newton back propagation, indicated using 34 datasets for training, 8 for validation and 8 for testing.…”
Section: 1mentioning
confidence: 99%
“…Chandwani et al [1] study on ready mix concrete modeling, the artificial neural network (ANN) model showed promising results in comparison to first-order and second-order regression techniques, for modeling unknown complex relationship exhibited by design mix proportion and concrete slump. Sathyan et al [2] used random kitchen sink algorithm and regularized least square to predict concrete rheological and hardened properties, results indicated RMSEs and mean absolute errors(MSEs) of less than 0.05. According to Revathy et al [3] the MAPE represent model performance and RMSE -Equation (3)-represent the error between the experimental and predicted results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [25] examined the deviation between predicted and experimental values using RMSE, mean absolute percentage error (MAPE) and absolute factor of variance (R 2 ), the equations (3) and (4). Chandwani et al [26] used six different statistical performance for evaluation that included mean absolute error (MAE) and mean absolute percentage error (MAPE) as shown in equations ( 5) and (6). Ngandu [10]…”
Section: Evaluation Of Network(s)mentioning
confidence: 99%
“…Revathy et al [5] carried out a study, where mean absolute percentage error (MAPE) represented the model performance and root mean square error (RMSE) represented the error between experimental and predicted results, for neural network models generated to predict compressive strength and fresh properties of flowable concrete, using MATLAB; they used 34 data set for training, 8 for validation and 8 for testing, using BFGS quasi-newton back propagation training algorithm for neural network. Sathyan et al [6] used random kitchen sink algorithm and regularized least square algorithm; the two applications come together in the grand unified regularized least square (GURLS) tool bar in MATLAB; the training data had 32 datasets and to measure model accuracy 8 test dataset were used; hardened stages of self-compacting concrete were used for modeling. Algorithms of HIV/AIDS model were developed under free GNU octave (5.1.0 version); results indicated the usefulness of computing systems like GNU octave as indicated by Campos et al [34].…”
Section: Introductionmentioning
confidence: 99%